Wage curve versus Phillips curve: a microeconomic estimation for the Spanish case (Análisis Económico, 2018)
The aim of this paper is to test for the existence of a wage curve for the Spanish economybetween 1994 and 1996. The results confirm the negative relation between the level of nominalwages and the unemployment rate in local labor markets. We also analyse whetherthere is a relation between the local unemployment rate and wage changes, as the Phillipscurve describes, with disaggregated data, introducing the lagged dependent variable intothe specification and check the value of its coefficient. The results do not permit us to affirmthat there is evidence of a Phillips curve relation.JEL Classification: J31, J60, J69.